Auditors experience as moderating effect investigative abilities and understanding of red flags on fraud detection - Narayana, Anak Agung Surya; Ariyanto, Dodik (International research journal of management, IT and social sciences, 2020)
This study was aimed to examine the auditor’s experience as moderating to the effect of investigative abilities and understanding of red flags on fraud detection. There are several factors that affect the detection of fraud is the investigative ability and red flags. But these factors have an inconsistent effect, and it is suspected that this is moderated by the auditor’s experience. This research was conducted at the state development audit agency (BPKP) province of Bali in 2019. The number of samples taken was 83 auditors who were willing to participate in this study. The sample in the study was determined by purposive sampling method. The data analysis technique used is Partial Least Square (PLS) analysis. Based on the results of the study it was found that higher investigative abilities make better the detection of fraud. The higher red flags, make better the fraud detection. The higher of auditor’s experience, make better the fraud detection. The more experienced of the auditor, can be stronger the effect of investigative abilities on fraud detection. The auditor’s experience is not able to moderate the effect of understanding of red flags on fraud detection, with R-square value (R2) of 82.3%.